Evaluation of dispersibility and resistance to simple compression of soil composites, construction and demolition waste and hydrated lime (Research, Society and Development, 2021)
Dispersive soil is a material that presents problems related to erodibility due to chemical phenomena, and requires techniques that enable the improvement of its characteristics for use. In this work, construction and demolition waste (RCD) was applied to replace the fraction of a dispersive soil from the island of Itamaracá, together with the addition of lime to improve dispersion and resistance to simple compression (RCS). The soil and the RCD were used in the production of composites, in percentages of 20%, 40% and 60% of RCD, and the hydrated lime added in levels of 3%, 5% and 7%. Physical, chemical, mineralogical and mechanical characterization tests were carried out, in addition to erodibility tests. The results indicated that the RCD when next to the lime, presents results superior to that of the soil, for 40% and 60% of RCD, from 3% of lime, reaching gains of up to 300%. Thus, as in RCS, for dispersiveness, the best results refer to the joint action of RCD and lime, with composites of 40% and 60% having the best performances. Thus, it is observed that it is feasible to improve the dispersiveness of the soil and the RCS by applying the RCD to replace part of the soil when added to the lime. In this way, the possibility of improving the characteristics of the dispersive soil is evidenced, together with an application for the RCD, for which a correct final destination is obtained, thus, a beneficial use under the sustainable aspect.